Health Support for a Remote Industrial Site - Thierry Lentz; Sabine Genty; Alain Gergereau; Alexis Descatha; Alexis Descatha; Alexis Descatha; Alexis Descatha; Alexis Descatha (Frontiers Media S.A., 2019)
This publication is derived from and rooted in the authors' experience in designing the Health Support of a remote industrial site. Summarizing the main steps of this design is the purpose of the approach. As a first step devoted to "Evaluation" (Chapters 1-5) are displayed the fundamentals for designing a Project Health Plan, such as a realistic and operative definition of "patient stabilization" and the principles of tactical reasoning for Medevacs, specifying how pathophysiology and logistic constraints should be correlated. A core element of the conceptual work consists in partnering these two domains, which usually each go their own way. Both should be considered in terms of delays: in life threatening situations, pathophysiology allows for a (maximum) delay before effective stabilization, while logistics dictates a (minimum) delay for reaching a stabilization facility. Ensuring that these two delays match is the desired result. Clearly, this conceptual work will unfold its full potential in low sanitary level countries, where most industrial commodities Projects take place, and where these delays are the longest. Next is detailed the audit/study preparation, i.e., the data gathering needed to get a clear picture of the Project conditions and concerns, workforce headcount and pattern, evacuation vectors and delays, and reference documents. Finally, risk assessment and a review of health facilities-in the vicinity and further away-complete the evaluation work. In a second phase devoted to "Implementation" (Chapters 6-9) is detailed how contracts with health providers, and health exhibits of industrial contracts should be conceived, and how on-site health support is designed, from the necessity of a pre-employment check to the design and organization of routine and emergency medicine facilities. Emergency preparedness and response plans, as well as medical coordination, should integrate with the HSE command chart. Overall, this document strongly advocates for joint engineering between HSE officers and medical specialists. An overview of key points for hygiene-often a separate topic covered in an offprint-is proposed. Finally, forward guidance for writing the audit/study report is proposed. This audit/study report must result in conclusive recommendations. Hence, a guide is proposed so that the report becomes a matrix of the Health Plan itself, and will be ended by a summary of findings and recommendations ready-to-use in Project management. In this way, the Health Plan will be launched, and gradually evolve and be amended as a "living document" throughout the lifetime of the Project.